Gait Variability among Healthy Adults: Low and High Stride-to-Stride Variability Are Both a Reflection of Gait Stability - Beauchet, Olivier; Allali, Gilles; Annweiler, Cédric; Bridenbaugh, Stephanie; Assal, Frederic; Kressig, Reto W.; Herrmann, François R. (Gerontology (Basel), 2009)
Background: It has been suggested that high stride-to-stride variability (STV) is a reflection of gait instability. However, both low and high STV has been shown in fallers and in nonfallers; therefore, the interpretation of STV of spatiotemporal gait parameters remains difficult. Thus, we sought to characterize and compare STV of spatial and temporal stride parameters among young and older healthy adults, and to determine the extent to which opposite results in STV could provide similar implications in terms of gait stability. Methods: Mean values of coefficients of variation of spatiotemporal gait parameters were collected from 30 young adults (14 men and 16 women; mean age 28.1 ± 6.0 years) and 33 older adults (2 men and 31 women; mean age 74.4 ± 7.1 years) walking at self-chosen normal walking speed over a GAITRite® System. Results: An age-related increase in STV was only observed with stride width (p = 0.012), whereas increased stride length and stance time variability in older adults were related to decreased walking speed (p = 0.006 and p = 0.018). In addition, both low and high STV was found in both groups of subjects and the highest value was observed for stride width (p < 0.001). Conclusion: The two main implications of the present results are that decreased walking speed should be taken into account when exploring age-related effects on gait variability, and that both low and high spatiotemporal STV may reflect gait stability in healthy adults.